Human pregnane X receptor is expressed in breast carcinomas, potential heterodimers formation between hPXR and RXR-alpha - Conde, Isabel (BioMed Central, 2008)
BACKGROUND: The human pregnane X receptor (hPXR) is an orphan nuclear receptor that induces transcription of response elements present in steroid-inducible cytochrome P-450 gene promoters. This activation requires the participation of retinoid X receptors (RXRs), needed partners of hPXR to form heterodimers. We have investigated the expression of hPXR and RXRs in normal, premalignant, and malignant breast tissues, in order to determine whether their expression profile in localized infiltrative breast cancer is associated with an increased risk of recurrent disease. METHODS: Breast samples from 99 patients including benign breast diseases, in situ and infiltrative carcinomas were processed for immunohistochemistry and Western-blot analysis. RESULTS: Cancer cells from patients that developed recurrent disease showed a high cytoplasmic location of both hPXR isoforms. Only the infiltrative carcinomas that relapsed before 48 months showed nuclear location of hPXR isoform 2. This location was associated with the nuclear immunoexpression of RXR-alpha. CONCLUSION: Breast cancer cells can express both variants 1 and 2 of hPXR. Infiltrative carcinomas that recurred showed a nuclear location of both hPXR and RXR-alpha; therefore, the overexpression and the subcellular location changes of hPXR could be considered as a potential new prognostic indicator.